Newborn care practices among slum dwellers in Dhaka, Bangladesh: a quantitative and qualitative exploratory study - Ahsan Karar Zunaid; Wahed Tasnuva; Uz Zaman Khan Nazib; Choudhury Nuzhat; Moran Allisyn C; Faiz Rashid Sabina; Alam M Ashraful (BMC, 2009)
Abstract Background Urbanization is occurring at a rapid pace, especially in low-income countries. Dhaka, Bangladesh, is estimated to grow to 50 million by 2015, with 21 million living in urban slums. Although health services are available, neonatal mortality is higher in slum areas than in urban non-slum areas. The Manoshi program works to improve maternal, newborn, and child health in urban slums in Bangladesh. This paper describes newborn care practices in urban slums in Dhaka and provides program recommendations. Methods A quantitative baseline survey was conducted in six urban slum areas to measure newborn care practices among recently delivered women (n = 1,256). Thirty-six in-depth semi-structured interviews were conducted to explore newborn care practices among currently pregnant women (n = 18) and women who had at least one delivery (n = 18). Results In the baseline survey, the majority of women gave birth at home (84%). Most women reported having knowledge about drying the baby (64%), wrapping the baby after birth (59%), and cord care (46%). In the in-depth interviews, almost all women reported using sterilized instruments to cut the cord. Babies are typically bathed soon after birth to purify them from the birth process. There was extensive care given to the umbilical cord including massage and/or applying substances, as well as a variety of practices to keep the baby warm. Exclusive breastfeeding was rare; most women reported first giving their babies sweet water, honey and/or other foods. Conclusion These reported newborn care practices are similar to those in rural areas of Bangladesh and to urban and rural areas in the South Asia region. There are several program implications. Educational messages to promote providing newborn care immediately after birth, using sterile thread, delaying bathing, and ensuring dry cord care and exclusive breastfeeding are needed. Programs in urban slum areas should also consider interventions to improve social support for women, especially first time mothers. These interventions may improve newborn survival and help achieve MDG4.